2018
DOI: 10.1007/s00449-018-1935-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined production of fucoxanthin and EPA from two diatom strains Phaeodactylum tricornutum and Cylindrotheca fusiformis cultures

Abstract: Fucoxanthin and eicosapentaenoic acid (EPA) provide significant health benefits for human population. Diatom is a potential natural livestock for the combined production of EPA and fucoxanthin. In this study, first, the effects of three important parameters including light intensity, nitrogen concentration and salinity were evaluated for the production of EPA and fucoxanthin in two diatom strains Phaeodactylum tricornutum and Cylindrotheca fusiformis. And then, two steps method based on light intensity were ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 24 publications
9
70
0
Order By: Relevance
“…Nevertheless, the results reveal that an increased biomass-specific product content (increase of around 20 %) is achieved at low light settings. These findings correlate with previous observations made for P. tricornutum on a molecular level [7] and are in line with data published for the cultivation of diatoms at reduced light intensity previously [11,37,56]. Our data show for the first time that the phenomenon of light adaption is valid for this particular P. tricornutum strain (UTEX 640) and thus, it can be used for the production of fucoxanthin-rich biomass with a biomass-specific fucoxanthin content of up to 20.1 ± 1.6 mg g -1 .…”
Section: Effect Of Light Availability On the Fucoxanthin And Epa Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, the results reveal that an increased biomass-specific product content (increase of around 20 %) is achieved at low light settings. These findings correlate with previous observations made for P. tricornutum on a molecular level [7] and are in line with data published for the cultivation of diatoms at reduced light intensity previously [11,37,56]. Our data show for the first time that the phenomenon of light adaption is valid for this particular P. tricornutum strain (UTEX 640) and thus, it can be used for the production of fucoxanthin-rich biomass with a biomass-specific fucoxanthin content of up to 20.1 ± 1.6 mg g -1 .…”
Section: Effect Of Light Availability On the Fucoxanthin And Epa Contentsupporting
confidence: 93%
“…However, it is worth mentioning that recent publications show the possibility to influence the product content as well as the volumetric productivity of diatoms by adjusting specific operating parameters during cultivation. Gao et al [36] and Wang et al [37] reported an effect of the nitrogen level, the light intensity and the salinity on the specific product content and volumetric productivity of EPA and fucoxanthin using P. tricornutum. An approach to extract both compounds as a lipid fraction with ''green'' organic solvents from P. tricornutum was demonstrated by Delbrut et al [38].…”
Section: Introductionmentioning
confidence: 99%
“…Although many microalgae are rich in fucoxanthin, their fucoxanthin productivity is often poor. Fucoxanthin-rich microalgae, including Mallomonas sp., Isochrysis galbana , Phaeodactylum tricornutum and Odontella aurita , have been reported to have high fucoxanthin content (1.65% to 2.66%), but the maximum fucoxanthin productivity only ranged from 1.75 to 7.96 mg/(L·d) [ 11 , 12 , 13 , 14 ]. The low productivity of fucoxanthin in these previous studies was likely due to inefficient utilization of organic carbon source(s) in the culture medium [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liquefaction is a thermal process that can convert biomass into liquid fuel at high temperatures (250-350 • C) and pressures (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and it is suitable for MRAE with high moisture [170]. MRAE of different species (Spirulina, Nannochloropsis, and Chlorella) have been applied to produce biofuel through the liquefaction process [177,178].…”
Section: Thermochemical Conversion Of Mraementioning
confidence: 99%
“…A specific marine microalgae species can be used as a feedstock for many different bio-compounds. For instance, Phaeodactylum tricornutum is a good candidate for fucoxanthin and EPA [12], Dunaliella salina can be used to produce proteins and carotenoids [13], and Spirulina sp. Can accumulate a large amount of carbonic anhydrase, C-phycocyanin, and allophycocyanin [14].…”
Section: Introductionmentioning
confidence: 99%